Microfluidic nanobubbles produced using a micromixer for ultrasound imaging and gene delivery - Taiki Yamaguchi; Yoko Endo-Takahashi; Kento Awaji; Seiyo Numazawa; Yuni Onishi; Rui Tada; Mitsuo Ogasawara; Yoshimasa Takizawa; Hitoshi Kurumizaka; Yoichi Negishi (Scientific Reports)
Abstract Ultrasound (US)-mediated delivery is considered relatively safe and achieves tissue-specific targeting by simply adjusting the application site of the physical energy. Moreover, combining US with micro- or nanobubbles (MBs or NBs), which serve as US contrast agents, enhances the delivery of drugs, genes, and nucleic acids which also functioning as a tool for US. The performance of US-responsive MBs and NBs, including their therapeutic outcomes, is influenced by the bubble manufacturing methods. Furthermore, productivity and scalability must also be considered for clinical applications. Among various NBs fabrication techniques, microfluidic technology has emerged as a promising approach. However, the potential of NBs generated by microfluidics for drug delivery remains unexplored. In this study, US-responsive NBs were prepared using a microfluidic device, providing a single step gas-filling operation and rapid production method not only for US imaging but also for gene delivery. The effectiveness of these NBs was subsequently evaluated. The preparation conditions for the microfluidic NBs (MF-NBs) were optimized based on their physical properties, including particle size, number concentration, and their performance as US agents. Gene delivery capability was assessed in various tissues, including muscles, heart, kidney, and brain. The results demonstrated that MF-NBs exhibit high monodispersity, enhance US imaging, achieve widespread distribution following administration (including in brain tissue), and enable gene delivery to irradiated areas. These findings suggest that MF-NBs, with their high productivity and uniformity, are promising candidates for practical applications in US imaging, gene delivery, and nucleic acid delivery systems.